Domi Bustomi HUBUNGAN ANTARA DAYA LEDAK OTOT LENGAN, KOORDINASI MATA-TANGAN, DAN RASA PERCAYA DIRI DENGAN HASIL KETERAMPILAN OPEN SPIKE BOLA VOLI - Bustomi, Domi (Universitas Nusantara PGRI Kediri, 2017)
ABSTRACT The research method used is a correlation method using Product Moment calculation techniques. Samples about 20 people that is all player / athlete men's volleyball Platda Karawang regency. The first results of hypothesis testing, we found a positive relationship between Explosive power arm muscle (X1) with the results of the Open Spike Volleyball Skills (Y), This means that the Explosive power arm muscle contributed as much as 68% of the results of the Open Spike Volleyball Skills. Second, there is a positive relationship between Eye-hand coordination (X2) with the results of the Open Spike Volleyball Skills (Y), It means that the eye-hand coordination contributed as much as 78% of the results of open spike volleyball skills. Third, there is a positive relationship between Self-Confidence (X3) with the results of the Open Spike Volleyball Skills (Y), That means that confidence contributed as much as 46% of the results of open spike volleyball skills. Fourth, there is a positive relationship between limbs power (X1), eye-hand coordination (X2), Self-Confidence (X3) with the results of the Open Spike Volleyball Skills (Y), This explosive power arm muscle, eye-hand coordination and self-confidence simultaneously contributed by 82% with the results of open-spike volleyball skills. So it can be concluded that the power limb, eye-hand coordination, and self-confidence have significant relation with outcome open spike volleyball skills. Key words: The Results, Open Spike, Volleyball Skills.